Hedonic price analysis of the internet recreational equine market - Freeborn, Jennifer (Kansas State University, 2009)
Hedonic pricing models have long been used to evaluate prices in high-end segments of the equine industry. However, the lower end markets, including most of the recreational and pleasure horses, have yet to be studied in the economic literature. This study evaluates characteristics affecting the price of recreational horses advertised online, and provides a framework for future market studies on various segments of the equine industry. Data were collected in both the spring and fall of 2008, in addition to a survey being conducted in the fall to collect more accurate pricing information. Three different functional forms were used and their outcomes discussed to determine which one best fit the data. Results show that the semi-log functional form appeared to best fit the data. Characteristics that consistently showed statistical significance included the horse being advertised using a photo ad, the age of the horse, and whether or not the horse was registered. Gender variables and the state which the horse was sold from showed statistical significance in most of the models; although the variables denoting breed were statistically significant as a group, no model consistently found statistical significance in any of the variables individually. Color characteristics did not demonstrate statistical significance consistently in any model. Finally, suggestions for future research are discussed. Data issues could be avoided with larger or more specific data sets; various data sources could be examined or created such as live equine auctions; regions could be examined by show or rodeo circuit instead of by state. There are political issues in the industry that need to be addressed, but a lack of available data needs to be examined and corrected before many issues can be thoroughly examined. The equine industry is often overlooked in economic literature and is a multi-billion dollar agricultural industry which deals with legislative and taxation issues just like the rest of the agricultural world and is deserving of attention.
Keywords: Equine pricing; Hedonic model; Horse market; Recreational; Internet; Agriculture, General (0473); Economics, Agricultural (0503)